Political Fragility and the Timing of Conflict Mediation - Carly Beckerman (Social Sciences, 2022)
In recent years, much of the public discourse regarding conflict in the Middle East has pondered the possibility of military intervention, but far less attention has been paid to the optimal mechanisms for conflict mediation. There remains considerable confusion in the study of conflict resolution about how to locate the right time, or ‘ripe moment’ for this type of third-party involvement. This is a crucial area of policy relevant research. When attempting to model ripeness, most of the literature has relied on expected utility models of decision-making and found that crucial but nebulous factors that are important in the MENA region, such as conflicting parties’ psychology, religious and political beliefs, as well as grievances compounded over time, cannot easily be incorporated into the framework. This paper offers a plausibility probe to highlight the potential of an augmented approach. Using Poliheuristic (PH) Theory that reflects the non-compensatory nature of political risk, it creates a litmus test for third-party mediation based not on what conflicting parties aim to achieve, but what outcomes and processes they must avoid. The result is a relatively simple identification of ‘bad’ timing, as well as theory-informed mechanisms designed to help practitioners generate better conditions for mediation. This probe contributes to our understanding of the relationship between political fragility and conflict in the MENA region by indicating how political fragility might be conceptualized as a process that can be mapped and perhaps interrupted.